Carbon dioxide and methane emission of denitrification bioreactor filling waste sawdust and industrial sludge for treatment of simulated agricultural surface runoff. (1st July 2021) - Luo, Hongbing; Zhuang, Daiwei; Yang, Jinping; Liu, Xiaoling; Zhang, Ke; Fu, Xiaoying; Jiang, Bing; Xue, Ru; Fan, Liangqian; Chen, Wei; Cheng, Lin; Chen, Fenghui; et al.
Abstract: Carbon dioxide (CO2 ) and methane (CH4 ) produced by denitrification bioreactors in processing agricultural surface runoff have contributed to increasing proportion of greenhouse gases (GHG) emissions. It is the first time to monitor and quantify the emission flux of CO2 and CH4 produced by laboratory-scale denitrification bioreactors which recycled waste Cunninghamia lanceolata sawdust (CLS) and industrial sludge (IS) as fillers to process simulated agricultural surface runoff. Sludge-water ratio, inflow rate and water flow direction are used as experimental factors to study the effect on the emission flux of CO2 and CH4 . Results show that emission flux of CO2 from denitrification bioreactors with different sludge-water ratio approached 20 mg m −2 h −1, simultaneously the average emission flux of CH4 produced by all bioreactors was 1.785 mg m −2 h −1 . The addition of sludge increased the emission flux of CH4 and had no significant effect on the emission flux of CO2 . Increasing the inflow rate reduced the CO2 emission flux from 21.57 to 1.27 mg m −2 h −1, and at the same time increased the CH4 emission flux from 0.007 to 9.54 mg m −2 h −1 . The gravity flow of wastewater reduced the emission flux of CO2 and CH4 . The emissions of CO2 and CH4 from folded plate denitrification bioreactor with CLS and industrial sludge with a volume ratio of 1:2 can be reduced by 24.67% and 73.3%, respectively. There was no need to add special gas collection and treatment devices because CO2 and CH4 emission fluxes produced by the folded plate denitrification bioreactor and gravity denitrification bioreactor are not enough to increase the greenhouse effect. This study quantified the CO2 and CH4 produced by denitrification bioreactors filling CLS and IS, and provided a reference for future research on the gases produced by the denitrification process. Highlights: Recycling waste Cunninghamia lanceolata sawdust (CLS) as biological carbon sources. Monitor and quantify the CO2 and CH4 emission produced by CLS and IS bioreactors. The CO2 emission flux produced by CLS and IS bioreactors is about at 20 mg. m −2 h −1 . The average emission flux of CH4 produced by all bioreactors is 1.785 mg. m −2 h −1 . The folded plate bioreactor reduces the emission flux of 24.67% CO2 and 73.3% CH4 .